Before and After Merger of Bank Performance Analysis - ra afera ratna wijayanti; fadhil athallah saputra; raden mohammad naufal alihassan (IULI Publisher, 2023)
The rapid development of the banking world has resulted in the need for mergers between banks, to make the banking world healthier and stronger in facing competition in the global economy as well as an increasingly competitive free market. The purpose of this study is to determine the performance of a bank that is doing a merger in Indonesia, seen from the measurement of thebprofitability ratios, the liquidity ratios, and the solvency ratios. The object used in this study is a banking company that joined and was registered on the Indonesia Stock Exchange within 2019. The sample in this study was 3 large Syariah bank companies using a purposive sampling method. This study uses comparative research and the data used is secondary data. The analytical method used is paired sample t-test. The results showed that in the liquidity ratio variable, there was a difference in company performance before and after the merger while in the profitability ratio and solvency ratio variable company performance, there was no difference before and after the merge. Key Words: Merger, profitability ratio, liquidity ratio, solvency ratio, performance.